Viridans Group Streptococci in Pediatric Leukemia and Stem Cell Transplant: Review of a Risk-stratified Guideline for Empiric Vancomycin in Febrile Neutropenia. Issue 9 (September 2021) - Ruhayel, Sandra D.; Foley, David A.; Hamilton, Kate; Ferguson, Patricia; Kotecha, Rishi S.; Bowen, Asha C.; Yeoh, Daniel K.
Abstract : Viridans group streptococci (VGS) are an important cause of sepsis in immunosuppressed children. We reviewed the effectiveness of risk-stratified addition of vancomycin to empiric febrile neutropenia therapy among 107 children with leukemia or undergoing an allogeneic transplant. Of 19 VGS bacteremia episodes, 78.9% were susceptible to risk-stratified antibiotics including 100% from high-risk patients. All blood cultures were flagged positive within 24 hours. Abstract : Supplemental Digital Content is available in the text.